Ovarian Basaloid Carcinoma with Shadow Cell Differentiation - Michal Zamecnik; Daniel Jando; Peter Kascak (Case Reports in Pathology)
So-called shadow cell differentiation (SCD) is typical for pilomatrixoma and other skin lesions with follicular differentiation, but it was rarely described also in some visceral carcinomas. We report a case of ovarian basaloid carcinoma with SCD. The tumor presented as a 14 cm ovarian mass in a 45-year-old woman, and therefore the adnexectomy and hysterectomy were performed. The tumor was of high stage. Multiple metastases were found in the liver, retroperitoneal and mediastinal lymph nodes, and the lung. Histologically, the tumor showed a pattern of high-grade basaloid carcinoma with numerous shadow cells. Extensive histologic examination did not reveal any glandular or preexisting teratoma component. Immunohistochemically, the tumor expressed markers of squamous cell differentiation, such as p63, cytokeratin 5/6, and high-molecular-weight keratin. Cytokeratin 7 and CA125 were positive in scattered cells of the lesion. Estrogen and progesterone receptor, vimentin, and p53 were negative. Beta-catenin showed nuclear and cytoplasmic positivity, indicating possible tumor proliferation/differentiation via Wnt signaling pathway. To our knowledge, SCD in basaloid carcinoma of the ovary was not described before. In addition to the description of the case, we review the literature on SCD in visceral carcinomas.